Model Sistem Reservasi Real-Time untuk Penginapan Berbasis Arsitektur Cloud dengan Metode Pengembangan ADDIE - Setiawan, Muhammad Ilham; Widodo, Tri (TIN: Terapan Informatika Nusantara, 2025)
The development of digital technology and cloud computing services has significantly transformed the tourism and accommodation sectors. Annisa Inn, located near Pattimura Airport in Ambon, still manages room reservations, souvenir sales, and shuttle services manually, which can lead to recording errors and service delays. This study specifically aims to design and implement a real-time reservation system model based on cloud architecture integrated with additional service features, using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development method. The resulting system integrates room reservation features, a catalog of traditional Maluku souvenirs, and shuttle services into a single web-based platform. The implementation of Backend-as-a-Service (BaaS) Supabase, along with the integration of payment gateway Midtrans and email notification service Brevo, supports real-time transaction automation and user communication. The system was tested using the black-box testing method to ensure that all functions operate according to user requirements. The main contribution of this research lies in providing an integrated cloud-based system model that can serve as a reference for digitalization implementation in small and medium-scale lodging businesses.